Phenomenological Study of the Application of Islamic Business Ethics in Fashion Sale and Purchase Trasactions - Vicki Luvian; Novi Puspitasari; Agus Mahardiyanto (Journal of Management Research and Studies, 2023)
The paper explores the impact of business growth on human life and emphasizes the neglect of ethics by some profit-driven entrepreneurs. It advocates for the integration of Islamic principles to guide business conduct, promoting a holistic approach and ethical boundaries based on the Qur'an and Hadith. Drawing parallels between Kant's deontology theory and Al-Ghazali's insights, the paper underscores the importance of grounding business actions in religious principles for a morally sound approach in the evolving economic landscape. This study aims to analyze the application of Islamic business ethics in buying and selling transactions based on the principles of unity, equilibrium, free will, responsibility, and benevolence at Althaf Moslem Store in Bogor, Indonesia. The research employs a qualitative method with a case study approach. Informant selection is determined using a purposive method, and observation serves as the primary data collection technique. The results indicate that Althaf Moslem Store has successfully implemented the principles of Islamic business ethics.